PENGARUH SISTEM PENYAMPAIAN JASA TERHADAP CITRA RUMAH SAKIT SWASTA TIPE C DI MAKASSAR - Abdul Haeba Ramli (Media Riset Bisnis & Manajemen, 2013)
The objective of research is to analyze about the influence of service delivery system to type C hospital image in Makassar. This analysis data used Structural Equation Modeling (SEM) to observe about interrelatedness between some variables.The population in this study is 225 persons of hospital medical patient in type C hospital in Makassar and spread to 75 hospital patients in Stella Maris hospital, 75 hospital patients in Akademis Jaury Yusuf Putra hospital, and 75 hospital patients in Grestelina hospital. The research result show that service delivery system composed of physical support and contact personal are significant and positif influence to type C hospital image in Makassar.